Biocompatible solid-state ion-sensitive organic electrochemical transistor for physiological multi-ions sensing - Moudgil, Akshay (2023)
Wearable bioelectronic sensors have gained tremendous prominence and applicability in healthcare technologies as they offer an alternative to traditional clinical testing and health monitoring. However, many challenges must be overcome for off-site and point-of-care commercial applications, including sensitivity, selectivity, multiple analyte detection, sample procurement technique, invasiveness, biocompatibility, and accurate real-time sensing. Specifically, a wearable sweat-based diagnostic biosensing platform offers a non-invasive way for rapid and real-time monitoring of various physiological biomarkers. This work develops a flexible solid-state organic electrochemical transistor with an extended sensing node for multi-ions sensing in the physiological range with high selectivity, fast response, and superior sensitivity. The solid-contact architecture is implemented for easy sample handling, processability, device miniaturization, and flexibility. For the first time, multiplexed ions (Na+, K+, Ca2+) sensing with the integration of ion-selective membranes and biocompatible semiconducting channel in an extended gate-solid-state organic electrochemical transistor (ExGSSOECT) is presented. The integrated ExG-SSOECT device platform exhibited improved performance amongst the available wearable sensors and offers great potential to be a suitable biochemical sensor in wearable bioelectronics.